Antibacterial effect of Dimethyl sulfoxide extract of Aloe vera (Aloe barbadensis) leaf gel against Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Klebsiella pneumoniae - Haque, Syed Didarul; Al Amin, Abu Md Mayeenuddin; Islam, Baishakhi; Nazneen, Nazia; Karim, Syeda Noorjahan; Rahman, Md Abdur (Mediscope, 2020)
An exploratory study based on laboratory experiment was carried out to determine the antibacterial effect of Dimethyl sulfoxide (DMSO) extract of Aloe vera leaf gel (DAE) against standard strains of Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Klebsiella pneumoniae in the Department of Pharmacology & Therapeutics in collaboration with the Department of Microbiology, Mymensingh Medical College, Mymensingh, Bangladesh. DMSO extract was used in five different concentrations (100, 200, 300, 400 and 500 μg/ml). Dose dependent inhibitory effect was seen against the test organisms using disc diffusion method. Zone of inhibition (ZOI) were 8 mm, 13 mm, 15 mm, 16 mm and 21 mm against S. aureus; 0 mm, 8 mm, 13 mm, 15 mm and 18 mm against P. aeruginosa; 8 mm, 11 mm, 13 mm, 16 mm and 20 mm against E. coli; 0 mm, 9 mm, 12 mm, 14 mm and 18 mm against K. pneumoniae at 100, 200, 300, 400 and 500 μg/ml respectively. The minimum inhibitory concentration (MIC) was assessed by broth dilution technique. The MICs of DAE for S. aureus, P. aeruginosa, E. coli and K. pneumoniae were 300 μg/ml, 400 μg/ml, 400 μg/ml and 450 μg/ml respectively. From the study it was observed that DMSO extract of Aloe vera leaf gel possesses antibacterial effect against the test pathogens. The findings highlight the need for further extensive study to detect and isolate the biologically active ingredients present in the Aloe vera leaves which are responsible for antibacterial effect. Hopefully, that would lead to the discovery of new and more potent antimicrobial agents originated from Aloe vera. Mediscope Vol. 7, No. 2: July 2020, Page 67-74